Visual detection and feature recognition of underwater target using a novel model-based method. (14th November 2018) - Ji, Daxiong; Li, Haichao; Chen, Chen-Wei; Song, Wei; Zhu, Shiqiang
Imaging is an important means to explore the ocean for underwater robotics. The diffuse attenuation coefficient of light in water is one of the most important optical properties of seawater. This article presents a model-based method to analyze the causes of distortion of underwater images. We built a platform for underwater image acquisition and target recognition. The model coefficients were calibrated with images captured underwater and in air. Experiments were carried out to verify the designed algorithm and the transmission error model. The experiments show that the presented method works well in improving the accuracy of feature extraction and recognition of underwater targets.